In pursuit of culture - Ahmad, Sayeed, 1931- (Dhaka : Printcraft, 2008)
Autobiographical memoirs of the author's travel to various countries of the world.
Donated by Rebecca Dipa Khan
Keywords: Ahmad, Sayeed, -- 1931- -- Travel; Male dramatists -- Bangladesh -- Travel; Bengali drama; Art historians -- Bangladesh -- Travel; Artists as art critics -- Bangladesh -- Travel